Pengembangan Tes Berbasis Keterampilan Berpikir Kritis pada Materi Struktur dan Fungsi Jaringan Tumbuhan Kelas XI SMA - Rahayu, Dyan; Mu’nisa, Andi; Azis, Andi Asmawati (Universitas Negeri Makassar, 2019)
Abstract. This research aims to develop test based on critical thinking skills and its relevance as an evaluation tools in garde XI senior high school which are valid, practical and can measure student critical thinking skills. The subject of this research were high school students of grade XI. The process of developing test based on critical thinking skills was carried out using the ADDIE development model consists of analysis, design, develop, implementation and evaluation. The test developed was 11 items representing 11 indicators of critical thinking. Based on the results of research, the average value of validity shows 4.42 and includes a very valid criterion. The results of the implementation at SMAN 8 Makassar show that the test is very practical with a practicality value of 4.53 with the percentage of student responses being 70% with good criteria. The results of item analysis were obtained by the eleven questions having good quality in terms of validity, reliability, level of difficulty and discrimination. The level of critical thinking skills possessed by students is 48% with moderate criteria.Keywords: test, critical thinking skills, ADDIE.